The Role of Dynamic miRISC During Neuronal Development - Nawalpuri, Bharti; Ravindran, Sreenath; Muddashetty, Ravi S. (Frontiers in Molecular Biosciences, 2020)
Activity-dependent protein synthesis plays an important role during neuronal development by fine-tuning the formation and function of neuronal circuits. Recent studies have shown that miRNAs are integral to this regulation because of their ability to control protein synthesis in a rapid, specific and potentially reversible manner. miRNA mediated regulation is a multistep process that involves inhibition of translation before degradation of targeted mRNA, which provides the possibility to store and reverse the inhibition at multiple stages. This flexibility is primarily thought to be derived from the composition of miRNA induced silencing complex (miRISC). AGO2 is likely the only obligatory component of miRISC, while multiple RBPs are shown to be associated with this core miRISC to form diverse miRISC complexes. The formation of these heterogeneous miRISC complexes is intricately regulated by various extracellular signals and cell-specific contexts. In this review, we discuss the composition of miRISC and its functions during neuronal development. Neurodevelopment is guided by both internal programs and external cues. Neuronal activity and external signals play an important role in the formation and refining of the neuronal network. miRISC composition and diversity have a critical role at distinct stages of neurodevelopment. Even though there is a good amount of literature available on the role of miRNAs mediated regulation of neuronal development, surprisingly the role of miRISC composition and its functional dynamics in neuronal development is not much discussed. In this article, we review the available literature on the heterogeneity of the neuronal miRISC composition and how this may influence translation regulation in the context of neuronal development.